The bone-protective mechanisms of active components from TCM drugs in rheumatoid arthritis treatment - Lu, Qingyi; Xu, Jie; Jiang, Haixu; Wei, Qiuzhu; Huang, Runyue; Huang, Guangrui (Frontiers in Pharmacology, 2022)
Rheumatoid arthritis (RA) is an autoimmune disease whose hallmarks are synovial inflammation and irreversible bone destruction. Bone resorption resulting from osteoclasts involves the whole immune and bone systems. Breakdown of bone remodeling is attributed to overactive immune cells that produce large quantities of cytokines, upregulated differentiation of osteoclasts with enhanced resorptive activities, suppressed differentiation of osteoblasts, invading fibroblasts and microbiota dysbiosis. Despite the mitigation of inflammation, the existing treatment in Western medicine fails to prevent bone loss during disease progression. Traditional Chinese medicine (TCM) has been used for thousands of years in RA treatment, showing great efficacy in bone preservation. The complex components from the decoctions and prescriptions exhibit various pharmacological activities. This review summarizes the research progress that has been made in terms of the bone-protective effect of some representative compounds from TCM and proposes the substantial mechanisms involved in bone metabolism to provide some clues for future studies. These active components systemically suppress bone destruction via inhibit joint inflammation, osteoclast differentiation, and fibroblast proliferation. Neutrophil, gut microenvironment and microRNA has been proposed as frontier focus.